Interview with Michael Welker - Van der Westhuizen, Hendrik (Acta Theologica, 2017)
Michael Welker recently visited the University of the Free State. As Senior Professor and Director of the Research Centre for International and Interdisciplinary Theology at the University of Heidelberg, Welker recently led a project and edited a book (with Michael Beintker and Albert de Lange) on the European Reformation, focusing on forty-eight cities and their Reformers. In light of this project and the five hundred year commemoration of the Reformations, a public lecture was held on the theme The European Reformation: A liberating educational revolution.